PANDANGAN ISLAM TERHADAP IDDAH CERAI MATI WANITA KARIR DIDESA KANDANG TEPUS KECAMATAN SENDURO KABUPATEN LUMAJANG - Siti Fatimatuzzahro, Beni Ashari, (UAS PRESS, 2022)
Women as citizens have the same rights and obligations as well as opportunities as a man to play a role in development in all fields. In such circumstances if the career woman is suddenly abandoned by her husband, her activities will be faced with religious provisions called iddah or ihdad. When her husband dies, they have to go through the iddah period, while the iddah that took place in the village of Kennel Tepus, Senduro sub-district, not all career women perform their iddah in accordance with sharia rules because of the demands of work and responsibility to support their families.research uses a qualitative method (field research) with a This phenomenological type of research. This research succeeded in concluding: 1) the practice of 'iddah divorcing for career women in Kandangtepus Village, Senduro Subdistrict, Lumajang Regency, which is in accordance with religious and shari'ah rules, although not all of them perform the 'iddah in full which has been explained in the hadith and the Qur'an' an, but sometimes they go out of the house to earn a living in order to support themselves and their children.. 2) that the Islamic view of the 'iddah of divorce and death for career women whose husbands live in death is the same as women in general, namely 4 months 10 days. and According to M. Quraish Sihab, Islam allows a woman who is experiencing iddah to leave the house to earn a living in order to support her life and her children after the departure of her husband.